Рассказы и очерки - Соколов-Микитов Иван Сергеевич (2007)
Экземпляры: Ершовская библиотека (20190319) / Инвентарный номер: 6441 / Цена: / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: С 59 / ГРНТИ: 17.82.30 / ББК: 84(2Рос-Рус)6